OPTIMASI FORMULA MI BEBAS GLUTEN BERBAHAN TEPUNG GEMBILI DAN MOCAF - Hidrotunnisa; Ayuningtyas, Laksmi Putri; Aldila, Livianinda Elza; Yuliasari, Hikmah (Jurusan Ilmu dan Teknologi Pangan Universitas Halu Oleo, 2025)
Noodles are typically made from wheat flour, which contains gluten, making them less suitable for individuals with gluten intolerance. This study aims to investigate the effect of the proportion of yam flour and mocaf on the quality of noodles and optimize the formula to achieve the best quality response from gluten-free dry noodles using a D-optimal design. The responses analyzed included cooking quality (cooking time and cooking loss) and texture profile (hardness, cohesiveness, springiness, and chewiness). The results showed that increasing the yam flour proportion (24,58-34,4%), combined with reducing mocaf proportion (24,57-14,75%), could decrease cooking time (7.3–6.3 minutes), cooking loss (14.51–10.17%) and increased hardness (248.12–857.48 gf), cohesiveness (0.45–0.75), springiness (0.46–0.78), and chewiness (97,60–330,35). The optimal formula was obtained in a composition of 34.39% gembili flour and 14.76% mocaf flour with a desirability value of 0.710. The characteristics of the best formulation results include a cooking time of 6.3 minutes, a cooking loss of 10.69%, a hardness of 662.42 gf, a cohesiveness of 0.70, a springiness of 0.78, and a chewiness of 249.91. Verification shows that the actual response value is within the predicted range, indicating that the model is valid for application in the development of gluten-free noodles from local ingredients.